Multi‐scale patterns in the occurrence of an ephemeral pool‐breeding amphibian. Issue 3 (7th March 2022) - Halstead, Brian J.; Rose, Jonathan P.; Clark, Denise; Kleeman, Patrick M.; Fisher, Robert N.
Abstract: Species distributions are governed by processes occurring at multiple spatial scales. For species with complex life cycles, the needs of all life stages must be met within the dispersal limitations of the species. Multi‐scale processes can be particularly important for these species, where small‐scale patterns in specific habitat components can affect the distribution of one life stage, whereas large‐scale patterns in land cover might better explain the distribution of other life stages. Using a conditional multi‐scale model, we evaluated which aspects of the landscape and local environment are most strongly related to occupancy patterns of western spadefoots ( Spea hammondii ). In northern and central California, the proportion of grassland land cover within 2 km of a site was positively related to the occurrence of the northern clade of the western spadefoot. At the pond scale, we found that western spadefoots were more likely to breed in pools with lower pH. Our results indicate that protecting remaining grasslands for adult spadefoots and ensuring multiple pools with diverse characteristics and hydroperiods so at least some pools result in successful breeding will likely be necessary to conserve western spadefoots, especially with a changing climate. Considering the processes that affect species distributions at multiple life stages and spatial scales is an essential component of effective conservation.